Spatiotemporal Changes and Obstacle Factors of Forest Ecological Security in China: A Provincial-Level Analysis - Yu, Honghong; Yang, Jiameng; Qiu, Mengyuan; Liu, Zhiyong (John) (Forests, 2021)
Under the background of China’s proposal to achieve “carbon neutralization and carbon peak”, it is an important task for each province to clarify their forest ecological security (FES) status. However, there is little understanding of the temporal and spatial evolution of forest ecological security and its influencing factors. Based on the Pressure-State-Response (PSR) model, this paper constructed a comprehensive evaluation index system for forest ecological security and used the CRITIC method and panel data to estimate the dynamic changes in FES for 31 provinces in China (excluding Hong Kong, Macao, and Taiwan) between 2009 and 2018. Furthermore, the obstacle degree model was used to determine the important obstacle factors affecting FES. The results showed that: (1) The comprehensive indices of FES of most provinces in mainland China were increasing, showing a good development trend during the study period; (2) subject to the limitations of resources and economic conditions, the FES at the provincial level showed significant spatial heterogeneity, which generally presents a distribution characteristic of “low in the western region and high in the central and eastern regions”; and (3) the primary obstacles restricting the improvement of FES level in most provinces of China were forest state indicators or input response indicators, followed by pressure indicators. Therefore, it is recommended to take targeted measures to reduce the intensity of forest cutting and the incidence of forest disasters, improve the utilization efficiency of forest resources, the productivity of forestland and the input-output level of forestry industry, and strengthen the training of professional talents and technical input according to the resource endowment condition of each province so as to improve the level of forest ecological security.